Nitrogen Uptake Efficiency and Total Soil Nitrogen Accumulation in Long-Term Beef Manure and Inorganic Fertilizer Application - Omara, Peter; Aula, Lawrence; Raun, William R. (International Journal of Agronomy, 2019)
Livestock manure is a common soil amendment for crop-livestock production systems. However, the efficiency of crop nitrogen (N) uptake from the manure-amended soil may not equate with that from inorganic N sources. +e objective of this paper was to determine the efficiency of N uptake, grain yield, and total soil nitrogen (TSN) accumulation in beef manure-amended soil compared to the inorganic N fertilizer-amended soil. Data (1990–2015) from a long-term continuous winter wheat (Triticum aestivum L.) fertility experiment at Stillwater in Oklahoma, USA, were used in this report. +ree of the six “Magruder Plot” treatments used in this study were manure, NPK plus lime (NPKL), and a check (no nutrients applied). Pre-plant N, P, and K were applied annually at 67, 14.6, and 27.8 kg·ha−1, respectively, while beef manure was applied every 4 years at 269 kgN·ha−1. +e results indicated that grain N uptake in the manure treatment (48.1 kg·ha−1) was significantly (p < 0.05) lower than that in the NPKL treatment (60.2 kg·ha−1). +is represents 20.1% efficiency of inorganic N uptake than the manure N uptake. +e average grain yield (1990–2015) from the manure and NPKL treatments was 2265.7 and 2510.5 kg·ha−1, respectively, and was not significantly different. +ere was a trend of TSN increase over the study period for both manure and NPKL treatments. +e average TSN from manure and NPKL treatments was 0.92 and 0.91 g·kg−1 soil, respectively, and was not significantly different. While no significant difference between manure and NPKL grain yield was observed, there was a significantly lower uptake efficiency of manure Ncompared to inorganic N. Furthermore, the low uptake efficiency of the manure Ncould suggest a potential for environmental pollution. Appropriate timing and application rate of manure N sources could optimize crop use efficiency and limit potential threat to the environment.
Keywords: Nitrogen; Soil Nitrogen Accumulation; Beef Manure; Inorganic Fertilizer Application